Can factors affecting complication rates for ureteric re‐implantation be predicted? Use of the modified Clavien classification system in a paediatric population. (27th July 2014) - Suer, Evren; Ozcan, Cihat; Mermerkaya, Murat; Gokce, Mehmet Ilker; Gulpinar, Omer; Telli, Onur; Soygur, Tarkan; Burgu, Berk
<x xml:space="preserve">Abstract</x> Objective To determine preoperative predictive factors of postoperative complications of ureteric re‐implantation in children by using the modified Clavien classification system (MCCS), which has been widely used for complication rating of surgical procedures. Patients and Methods In all, 383 children who underwent ureteric re‐implantation for vesico‐ureteric reflux (VUR) and obstructing megaureters between 2002 and 2011 were included in the study. Intravesical and extravesical ureteric re‐implantations were performed in 338 and 45 children, respectively. Complications were evaluated according to the MCCS. Univariate and multivariate analyses were used to determine predictive factors affecting complication rates. Results In all, 247 girls and 136 boys were studied. The mean (sd) age was 46 (25) months and the mean (sd) follow‐up was 49.4 (27.8) months. The mean (sd) hospitalisation time was 4.7 (1.6) days. Complications occurred in 76 (19.8%) children; 34 (8.9%) were MCCS grade I, 22 (5.7%) were grade II and 20 (5.2%) were grade III. Society of Fetal Urology (SFU) grade 3–4 hydronephrosis, obstructing megaureters, a tailoring‐tapering and folding procedure, refractory voiding dysfunction and a duplex system were statistically significant predictors of complications on univariate analysis. Prior injection history, paraureteric diverticula, stenting, gender, age, operation technique (intra vs extravesical) were not significant predictors of complications. In the multivariate analysis refractory voiding dysfunction, a tailoring‐tapering and folding procedure, obstructing megaureters (diameter of >9 mm) and a duplex system were statistically significant predictors of complications. Conclusion Ureteric re‐implantation remains a valid option for the treatment of certain patients with VUR. Refractory voiding dysfunction, a tailoring‐tapering and folding procedure, obstructing megaureters (diameter of >9 mm) and associated duplex systems were the main predictive factors for postoperative complications. Use of a standardised complication grading system, such as the MCCS, should be encouraged to allow the valid comparison of complication rates between series.